1984
DOI: 10.1207/s15516709cog0803_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Mental Model in Learning to Operate a Device*

Abstract: This report presents three studies concerned with learning how to operate a simple control panel device, and how this learning is affected by understanding a device model that describes the internal mechanism of the device. The first experiment compared two groups, one of which learned a set of operating procedures for the device by rote, and the other learned the device model before receiving the identical procedure training. The model group learned the procedures faster, retained them more accurately, execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(184 citation statements)
references
References 3 publications
3
177
0
4
Order By: Relevance
“…Similarly, such a mental model may allow users to backtrack more easily if the user gets lost within the system. Previous research has clearly demonstrated the benefits to performance of having such models (e.g., Kieras & Bovair, 1984). However, the need to create and use system representations may place demands on spatial ability (Gilbert & Rogers, 1999), which may be problematic for older adults.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Similarly, such a mental model may allow users to backtrack more easily if the user gets lost within the system. Previous research has clearly demonstrated the benefits to performance of having such models (e.g., Kieras & Bovair, 1984). However, the need to create and use system representations may place demands on spatial ability (Gilbert & Rogers, 1999), which may be problematic for older adults.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Kieras & Bovair (1984) adopted this terminology to describe a mental model held by a user of how a device works. It includes a set of conceptual entities and their interrelationships (Payne , 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Norman (1986) emphasises that the appropriateness of the user's underlying model of a system is essential when troubleshooting, as the user is able to derive possible courses of action and possible system responses. Kieras & Bovair (1984) concluded that for very simple devices or procedures, there will be little value in providing a device model to users. Manktelow and jones (1987) warn that systematic errors may result from an inappropriately simple mental model.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, visual aids are directly able to facilitate internal mental imagery that can enable the attainment of task-related goals (e.g. Kieras and Bovair 1984).…”
Section: The Interconnections Between Mental Representationsmentioning
confidence: 99%
“…Device Model A device model is an individual's understanding of how a device works in terms of its internal structure and processes (Kieras and Bovair 1984). Spatial Visualisation Spatial visualisation is described as a type of representation that can be used to solve mechanical problems (Hegarty et al 2003).…”
Section: Termmentioning
confidence: 99%